The Role of Computerized Knowledge Operations in Improving Business Performance - حسين حسين وليد; سلمان ناظم جواد (Journal of Economics and Administrative Sciences, 2011)
This research aimed at studying the role of calculated knowledge an its efficiency in improving the performance especially most of the organizations are living within knowledge era which concentrate on new technology investment in different fields of modern live . Under the scientific trends towards the economy of calculated knowledge which depend basically on new computer program in order to utilize the knowledge to raise the level of work performance exploiting different resources in the best way that helps the organizations to achieve their objectives because the information technology and computer programs became a means of survival and indispensible instrument within the developed world which depend on prosperity . progress and competitive capabilities , Regarding application sides , it was represented in preparing questionnaire form including two central parts ; the first dealing with calculated knowledge , the second one dealing with work performance . the aim is to measure the effect of calculated knowledge over work performance . this research has been applied in general company for Iraqi Railway through distribution of forms among the company staff . All the data is entered and analyzed by using (SPSS) statistic program , and finally reached some conclusions and recommendations which may cherish the knowledge in this sector .